Meshless natural element method for nonlinear analysis of composite plates - Somireddy, Madhukar; Rajagopal, Amirtham (Journal of Structural Engineering, 2025)
In the present work, the geometrical nonlinear analysis of laminated composite plates is done using natural element method. The C¹ natural neighbor interpolation function is implemented for geometric nonlinear analysis. The first order shear deformation plate theory is adopted for plate analysis. The geometric nonlinearity is based on the von Kármán’s assumptions. The nonlinear static analysis is carried out with step loading and Newton-Raphson iterative method. The formulation developed here is validated with available analytical and finite element results. The effect of plate aspect ratio on deflection has been studied.